The Diplomacy of Small States: Exploring Opportunities and Limitations in the Case of Timor-Leste - O. A. Krasnyak; P. S. Shaternikov (Vestnik MGIMO-Universiteta, 2023)
This article examines the diplomacy of small states, focusing on the case of TimorLeste. It analyzes the foreign policy strategies of small states, which encompass bilateral and multilateral diplomacy, engagement in international organizations and global governance, and the utilization of public diplomacy. These diplomatic tools enable small states to pursue their foreign policy objectives despite their limited resources, while also fostering cooperative relationships with larger powers. Diplomacy is regarded as a universal mechanism through which small states like Timor-Leste can integrate into the global international relations system.Given the inherent limitations of small states in contesting with major and middle powers, they seek to enhance their international influence through collective actions, such as forming or joining coalitions in international organizations or intergovernmental forums. Additionally, small states employ public diplomacy to draw attention to their issues and needs, thereby reducing their reliance on greater powers and forging more advantageous collaborations with other states. Strategies such as imitation and balancing, participation in coalitions, promotion of international initiatives, provision of expertise, and adherence to the principles of international law are utilized to cultivate a positive image of small states as responsible actors in international relations and reliable partners.The article concludes that Timor-Leste has been successful in maintaining bilateral and multilateral relations and actively participating in international organizations. However, it faces systemic challenges in effectively employing public diplomacy mechanisms. These challenges can be attributed to underdeveloped national public institutions and the enduring influence of greater powers, which affect not only Timor-Leste but also the wider region.